Analysis of Tourism Education Mapping based on Region and Expertise Concentration to Improve the Quality of Tourism Services in the City of Bandung - Suwandi, Andreas; Oce Ridwanudin, Oce Ridwanudin; Asep Maosul, Asep Maosul; Affero Ismail , Affero Ismail (Journal of Tourism and Creativity, 2025)
The variation in the distribution of Tourism Vocational High Schools based on region and the concentration of expertise offered as learning centers for vocational secondary education is crucial so that tourism in the city of Bandung and throughout Indonesia can be managed and maintained well in a sustainable manner in accordance with the principles of Sustainable Development Goals (SDGs). ). Therefore, this research was conducted with the aim of analyzing and knowing the distribution of tourism vocational high schools based on region and concentration of expertise in the Bandung City area using descriptive qualitative research methods through literature studies via the Bandung City Education Department website.